2009
DOI: 10.1111/j.1574-6941.2009.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic oxidation of dimethylsulfide and methanethiol in mangrove sediments is dominated by sulfate-reducing bacteria

Abstract: The oxidation of dimethylsulfide and methanethiol by sulfate-reducing bacteria (SRB) was investigated in Tanzanian mangrove sediments. The rate of dimethylsulfide and methanethiol accumulation in nonamended sediment slurry (control) incubations was very low while in the presence of the inhibitors tungstate and bromoethanesulfonic acid (BES), the accumulation rates ranged from 0.02-0.34 to 0.2-0.4 nmol g FW sediment(-1) h(-1), respectively. Degradation rates of methanethiol and dimethylsulfide added were 2-10-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…However they noted little variation in diversity in the first 30 cm of that sediment [35]. In anaerobic sediments, SRB play an important role in nutrient cycling and organic matter remineralization [6], and they can be especially important in oil-polluted locations where certain SRB are capable of anaerobic hydrocarbon degradation [11]. Taketani and colleagues confirmed the importance of SRB populations in mangrove sediments, particularly after an oil-contamination event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However they noted little variation in diversity in the first 30 cm of that sediment [35]. In anaerobic sediments, SRB play an important role in nutrient cycling and organic matter remineralization [6], and they can be especially important in oil-polluted locations where certain SRB are capable of anaerobic hydrocarbon degradation [11]. Taketani and colleagues confirmed the importance of SRB populations in mangrove sediments, particularly after an oil-contamination event.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity and organic matter availability vary in different parts of mangrove forests [5]. Beneath a thin aerobic surface layer, mangrove sediments are predominantly anaerobic, i.e., anaerobic biochemical processes are catalyzed by sediment microbial communities [6]. In previous studies about microbial populations, it was shown that Alphaproteobacteria dominated the bacterial community in a non-disturbed Brazilian mangrove sediment [5] and that after crude oil exposure, bacterial groups such as Anaerolinea decrease in population abundance whereas Deltaproteobacteria increase [7].…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic respiration and the anaerobic reduction of sulfate are generally considered the most important respiration processes in mangroves (Alongi 2002;Kristensen et al 2008). For instance, Lyimo et al (2009) investigated the anaerobic oxidation of dimethylsulphide and methanethiol in Tanzanian mangrove sediments and described that this process is dominated by sulfate-reducing bacteria (SRB). Taketani et al (2010) evaluated the diversity of sulfate-reducing bacteria in a pristine mangrove sediment using denaturing gradient gel electrophoresis (DGGE) and a dissimulatory sulphate reductase (dsrB) gene clone library.…”
Section: Microorganisms In Mangrovesmentioning
confidence: 99%
“…Microbial metabolism of OSCs has been documented in numerous aerobic environments, as well as anaerobic fresh water, estuarine, salt marsh, mangrove, and hypersaline sediments (Kiene & Visscher, 1987;Lomans et al, 1999bLomans et al, , 2002aVisscher et al, 2003;Lyimo et al, 2009). In low-temperature anaerobic environments, methanogens and sulfate reducers are the dominant OSC consumers and compete for S-bearing organic compounds (Kiene et al, 1986;Kiene & Visscher, 1987;Lomans et al, 1999cLomans et al, , 2002bVisscher et al, 2003;Lyimo et al, 2009). In low-temperature anaerobic environments, methanogens and sulfate reducers are the dominant OSC consumers and compete for S-bearing organic compounds (Kiene et al, 1986;Kiene & Visscher, 1987;Lomans et al, 1999cLomans et al, , 2002bVisscher et al, 2003;Lyimo et al, 2009).…”
Section: Mesophilic Osc Metabolismsmentioning
confidence: 99%
“…Methanogens using MSH and DMS in their metabolism dismutate the carbon, producing methane and bicarbonate in a 3:1 ratio (de Bok et al, 2006). Consumption of MSH and DMS by sulfate reducers has been observed in a variety of anaerobic sediments (Kiene & Visscher, 1987;Lomans et al, 1999bLomans et al, , 2002aVisscher et al, 2003;Lyimo et al, 2009); however, the ability of sulfate reducers to metabolize OSCs was documented primarily through inhibition experiments (Kiene et al, 1986;Kiene & Visscher, 1987;Lomans et al, 1999bLomans et al, , 2002aVisscher et al, 2003), and only a few organic sulfur metabolizing sulfate reducers have been isolated. Consumption of MSH and DMS by sulfate reducers has been observed in a variety of anaerobic sediments (Kiene & Visscher, 1987;Lomans et al, 1999bLomans et al, , 2002aVisscher et al, 2003;Lyimo et al, 2009); however, the ability of sulfate reducers to metabolize OSCs was documented primarily through inhibition experiments (Kiene et al, 1986;Kiene & Visscher, 1987;Lomans et al, 1999bLomans et al, , 2002aVisscher et al, 2003), and only a few organic sulfur metabolizing sulfate reducers have been isolated.…”
Section: Organic Sulfur Metabolisms In Hydrothermal Environments 321mentioning
confidence: 99%